THE EFFECT DIRECTED READING THINKING ACTIVITY (DRTA) STRATEGYON STUDENTS’ READING COMPREHENSION: (An Experimental Study in STKIP Kusuma Negara Jakarta) - Megawati (English Education Department, 2019)
This research conducted in STKIP Kusuma Negara Jakarta. It uses experiment method who 40 students first semester. This research purposes: (1). To know result of the research which doesn’t use DRTA strategy. (2). To knowresult of the research which use DRTA strategy. (3). To know the effect Directed Reading Thinking Activity (DRTA) on Students’ Reading Comprehension. Method of the research is experiment. It consists of 40 students. There are 20 students group experiment class and 20 students groupcontrol class. Instrument reading comprehension is multiple choice, as much as twenty items. It uses random sampling technique. Test data analysis use homogeneity test and normality test, in order that it can proceed with the analysis of statistical parametric. Analysis results and hypothesis obtained (1). students’reading comprehension using DRTA strategies: mean = 85.80; median= 85.50 ; variance= 22.695; (2). students’ reading comprehension using conventional learning: mean =68.65 ; median= 68.00 ; variance=18.766. (3). There is significant effect directed reading thinking activity (DRTA) towards students’reading comprehension. It can be seen that t-score was 21.291 and sig.=0.000 < 0.05. It can be concluded that DRTA strategies give effects to increase students’ability in reading comprehension. Student encourage to give prediction and think the reading text. DRTA strategies suitable to apply in teaching reading comprehension in STKP Kusuma Negara Jakarta.